Unidad de Cuidados Continuos y Paliativos del Hospital Clínico Universidad de Chile - Palma B., Alejandra; LLanos V., Osvaldo (Revista Hospital Clínico Universidad de Chile, 2015)
Palliative care (PC) is recognized by the World Health Organization as a key component in the fight against chronic diseases and defined as “an approach that improves the quality of life of patients and their families facing the problem associated with life-threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial and spiritual.” In Chile PC has intensely developed in the last two decades and consequently has become an urgent need to establish academic centers that provide knowledge and skills necessary to ensure the quality of provided care. The Continuous and Palliative Care Unit (CPCU) of the Clinical Hospital of the University of Chile was raised as a project of the Medical Management and under supervision of the Internal Medicine Department. In this article we summarize the overall background and current importance of CP, the vision and mission of the CPUC as well as its structure and goals for the first 12 month of operation.